Gendered differences in perceptions and reports of wellbeing: A cross-sectional survey of adults on ART in Malawi. Issue 12 (2nd December 2022) - Moucheraud, Corrina; Paul-Schultz, Jenna; Mphande, Misheck; Banda, Ben Allan; Sigauke, Hitler; Kumwenda, Verwoed; Dovel, Kathryn; Moses, Agnes; Gupta, Sundeep; Hoffman, Risa M.
ABSTRACT: Few studies have examined gender differences in reported quality of life among persons living with HIV (PLWH) in low-income countries. We conducted a cross-sectional survey of adults on antiretroviral therapy in Malawi, including questions focused on wellbeing, and collected clinical data on these respondents. We compared men's and women's self-reported health and wellbeing using Poisson models that included socio-demographic covariates. Approximately 20% of respondents reported at least one physical functioning problem. In multiple variable models, men were significantly more likely to have a high viral load (≥200 copies/mL; aIRR 2.57), consume alcohol (aIRR 12.58), receive no help from family or friends (aIRR 2.18), and to feel worthless due to their HIV status (aIRR 2.40). Men were significantly less likely to be overweight or obese (aIRR 0.31), or report poor health (health today is not "very good;" aIRR 0.41). Taken together, despite higher prevalence of poor self-rated health, women were healthier across a range of objective dimensions, with better viral suppression, less alcohol use, and less social isolation (although they were more likely to have an unhealthy BMI). Research that includes multi-dimensional and gender-specific measurement of physical, mental and social health is important for improving our understanding of well-being of PLWH.